Motivational connections in language classrooms: A research agenda. (April 2021) - Henry, Alastair
Abstract: With roots in social psychology, second language (L2) motivation has largely been investigated using self-report techniques. Studies drawing on observational data gathered in contexts where learning takes place are rare, and understandings of how motivation evolves in classroom interactions remain limited (Boo, Dörnyei, & Ryan, 2015 ). In a position paper in Language Teaching, Ushioda (2016 ) maps out an agenda for qualitative research examining motivation that emerges in language classrooms. With a focus on psycholinguistic processes, and with the aim of understanding how motivation 'connects with specific aspects of second language acquisition [and] particular features of linguistic development', Ushioda makes the case for researching L2 motivation 'through a small lens' (p. 564). Furthering this agenda, I make proposals for research with a relational focus where, through a somewhat wider lens, motivation and engagement generated through connections created by teachers in their classroom practice can be investigated. To frame these proposals, I use the concept of connective instruction (Martin & Dowson, 2009 ). Connective instruction holds that motivation and engagement increase when students can connect with the teacher as a person, with content that the teacher enables them to get involved with, and with the working methods that the teacher promotes.